On the presence, distribution and conservation status of Lycopodium lagopus (Lycopodiaceae) in Italy - TROIA, Angelo; RAIMONDO, Francesco Maria; Greuter, W. (country:IT, 2014)
During our work on the Lycopodiaceae account for the upcoming Flora Critica d’Italia (1, 2), we assessed and accepted the presence in Italy of Lycopodium lagopus (Laest. ex Hartm.) Zinserl. ex Kuzen. = L. clavatum subsp. monostachyon (Grev. & Hook.) Selander (2). Already reported by Fiori (3) as L. clavatum f. monostachyum Desv., its presence in Italy was more recently confirmed by Tribsch & Schönswetter (4) and accepted in some subsequent regional works (e.g. 5, 6), but the taxon is not recognized as distinct in the last national checklist of vascular plants (7). Lycopodium lagopus has an arctic-alpine distribution in America and Eurasia (8, 9). Initially described as a variety of L. clavatum L., the taxon was later raised to subspecific (e.g. 10, 11) and specific rank (8, 9). In view of its largely sympatric occurrence with L. clavatum in the Alps, and of the apparent absence of intermediate populations or individuals, we prefer to treat L. lagopus as a separate species. The main characters distinguishing L. lagopus from L. clavatum are the number of strobili (usually 1, rarely 2), and especially their being sessile or subsessile on a 0-2 cm long “peduncle”. In the Italian Alps it usually occurs at >1800 m a.s.l. As a result of our revision of specimens in several Italian herbaria, this clubmoss, formerly known only from Trentino - Alto Adige and Lombardy, is here reported for the first time for Piedmont on the basis of two specimens collected by Carestia in Valsesia in 1870 and preserved in TO. The presence in Friuli - Venezia Giulia (reported in 6 on the basis of a posthumous work of Gortani) is not confirmed: a specimen collected by Gortani in 1908 and preserved in MFU under “L. clavatum f. monostachyum Desv.” is referable to L. clavatum. On the other hand, in view of the specie’s ecology and confirmed distribution, one may reasonably expect that it is to be found, additionally, in Val d’Aosta and Veneto. Lycopodium species in Europe have experienced a decline in abundance in a general way, ...